A study on the compensation for abused spouses under the Domestic Violence Act 1994 / Faiz Fahmi Md Fodzi … [et al.] - Md Fodzi, Faiz Fahmi; Abdul Rahim, Sarah; Rosli, Nur Atiqah; Mohd Ayem, Norsyafiqka (2014)
This research aims to ascertain the relevant principles and policies which may be used by the courts in compensating the abuse spouses in domestic violence in Malaysia under Section 10 of the Domestic Violence Act (DVA) 1994. The methodology employed in this research is doctrinal in nature and library based where we have to ascertain certain then principles which underline Section 10 of the Domestic Violence Act 1994. The findings from this research shows that there are four general principles when awarding compensation under Section 10 of the DVA 1994. They are compensation awarded for the pain and hurt suffered by the victim, compensation to redress financial support, compensation enables the domestic violence victim to leave an abusive relationship and the compensation claim that has potential to empower the victim. It is recommended that the local courts would adhere their principles in awarding compensation.